HARMONY, HEALING, AND SPIRITUALITY TOURISM: WESTERN TOURISTS ENGAGEMENT WITH MELUKAT RITUALS IN BALI - I Nengah Suardhana; I Gusti Bagus Rai Utama; I Wayan Kartimin; Anak Agung Ayu Ratih Kesumadewi (International Journal of Social Science, 2026)
Bali has emerged as a leading global destination for spiritual and wellness tourism, attracting Western travelers in search of personal transformation and inner healing. Among its distinctive cultural practices is the Balinese purification ritual, known as melukat, which employs sacred water as a medium for spiritual cleansing. This study explores the interaction between Western tourists and Balinese spiritual practices, with a particular focus on how melukat is experienced and interpreted within a cross-cultural context. A qualitative research design was adopted, utilizing in-depth interviews and participant observation conducted at selected sacred sites and wellness centers across Bali. The collected data were analyzed thematically to identify key patterns related to tourists’ motivations and processes of meaning-making. The findings reveal four primary motivations driving participation: (1) the desire to escape the pressures of modern life, (2) the search for authentic spiritual experiences, (3) the pursuit of holistic healing, and (4) a fascination with the perceived harmony of Balinese culture. At the same time, the study indicates that many participants reinterpret melukat through individualistic and psychological frameworks, often distancing the practice from its original religious and cosmological significance. Rather than representing a straightforward process of commodification, these interactions reflect a dynamic process of cultural adaptation and transformation. In this process, local communities actively engage with tourism while striving to preserve the core values of their spiritual traditions. This study contributes to the growing body of literature on spiritual tourism by offering a cross-cultural perspective on the reinterpretation of sacred rituals within global tourism contexts. It also underscores the importance of balancing tourism development with cultural preservation to ensure the long-term sustainability and authenticity of Bali’s cultural heritage.